Key transportation indicators summary of a workshop - National Research Council (U.S.). Committee on National Statistics; Casey, Jamie; Norwood, Janet Lippe; ebrary, Inc.; Workshop on Key Transportation Indicators (2000 : Washington, D.C.) (Washington, D.C. : National Academy Press, 2002)
"The purpose of the Worksshop on Transportation Indicators was to discuss issues relating to transportation indicators and provide the Bureau of Transportation Statistics with new ideas for issues to address."--P. 1.
"The NRC's Committee on National Statistics and its Transportation Research Board, which conducted these studies, convened a workshop on June 13, 2000"--P. 1.
Includes bibliographical references.
Electronic reproduction.
Keywords: Transportation -- United States -- Statistical services; United States -- Statistical services; Electronic books